Automotive electricity and electronics - Santini, Al (Delmar Cengage Learning, 2013)
Today's automotive technicians need a thorough understanding of electrical principles and electronic systems to service modern vehicles. This book explores how automotive electronics work, the role they play in a vehicle's normal operation, how and why technicians use test instruments, and common diagnosis and repair procedures.